EMPLOYEE SALARY INFORMATION SYSTEM OFF LABOR DEPARTMENT DATA MANAGEMENT IN PT INFOMEDIA NUSANTARA USING MICROSOFT ACCESS 2000 - Heny Damiyati; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2005)
With this system freelance payroll was on time. The calculation of overtime pay and freelance employees are in accordance with the realization that exist. Similarly, in terms of salaries of employees reporting to the CEO was on time. These errors may arise because of human error or other things that might happen.